Reputation and perverse transparency under two concerns. - Andina-Díaz, Ascensión; García-Martínez, José A. (Elsevier, 2023)
Quite often an expert takes position on an issue where certain actions can be perceived as biased. If the expert has an informational concern and she does not want the listener to perceive her as biased, she has an incentive to avoid the biased action, even if she thinks this is the correct action. This paper shows that when an expert has multiple types and two concerns, an informational concern and a bias concern, the incentive to contradict private relevant information and avoid the biased action can even increase when the listener observes the quality of the expert’s advice. We provide necessary and sufficient conditions for this perverse effect of transparency on consequences to emerge and discuss variations of the model.
Keywords: Información; Contradicción; Multiple types; Career concerns; Transparency on consequences; Perverse effect